A protein@metal-organic framework nanocomposite for pH-triggered anticancer drug delivery - Liang, Zuozhong; Yang, Zhiyuan; Yuan, Haitao; Wang, Chun; Qi, Jing; Liu, Kaiqiang; Cao, Rui; Zheng, Haoquan (Dalton transactions : an international journal of inorganic chemistry, 2018)
We have synthesized a core@shell nanocomposite using biocompatible bovine serum albumin (BSA) as the core and a pH-sensitive metal-organic framework (MOF) as the shell. Doxorubicin (DOX)/BSA nanoparticles as cores have been prepared. A zeolitic imidazolate framework-8 (ZIF-8) layer has been coated on the outer surface of the DOX/BSA core. The ZIF layer acts as a capsule for the safe storage of DOX under physiological conditions. An efficient pH-responsive drug delivery system using a BSA/DOX@ZIF, in which the drug is not released in PBS at pH 7.4 but is released at low pH (5.0-6.0), has been constructed. Compared to the pure ZIF, a better biocompatibility has been obtained using the BSA/DOX@ZIF. The BSA/DOX@ZIF shows a much higher efficacy than free DOX against the breast cancer cell line MCF-7. The positive charges on the outer surface of the BSA/DOX@ZIF also improve its cellular uptake. We have synthesized a core@shell nanocomposite using biocompatible bovine serum albumin (BSA) as the core and a pH-sensitive metal-organic framework (MOF) as the shell.